LEKSIKON PERBATIKAN PEKALONGAN (Kajian Etnolinguistik) - Nur Fatehah (Adabiyyāt: Jurnal Bahasa dan Sastra, 2010)
This research discusses batik lexicon in Pekalongan. The aims of this research are (1) to classify and to describe lexicon of batik-ness in Pekalongan; (2) to uncover the functions of lexicon of batik-ness in Pekalongan; and (3) to explain a reflection of cultural indication based on lexicon of batik-ness. This research uses ethnolinguistics approach as linguistic approaches, analyzing the relationship between language and culture, especially to observe how a language is used in daily routines as a means of communication of a particular society. The development in a cultural aspect (economy, social, religion, arts, science and technology, and so on) is reflected on its lexicon. Lexicon rises along with human needs to identify the existing products of culture. The lexicon of batik-ness in Pekalongan becomes the "wealth" of Pekalongan society. The lexicon of batik-ness in Pekalongan is relatively various and excessive. It is equivalent with the development of batik in Pekalongan. The lexicon of batik-ness in Pekalongan can be classified into batik tools; the name of batik fabric related to the batik place, which is produced; raw material; production process; and the style of illustration and motif. The functions of lexicon of batik-ness are as the treasure of language; the social identity of gendered job division; social identity based on economic strata; religion identity; and as a frame of coastal area culture. The culture based on the lexicon of batik-ness in Pekalongan realized in daily utterances existing in Pekalongan society.